A Frequency Modulation Fingerprint-Based Positioning Algorithm for Indoor Mobile Localization of Photoelectric Modules - Duan, Chi; Tian, Lixia; Bai, Pengfei; Peng, Bao (Frontiers in Physics, 2021)
Optoelectronic modules have a wide range of applications in the field of wireless communication. However, the function of mobile localization has not been realized in optoelectronic modules. In this paper, an indoor positioning algorithm, which was based on frequency modulation (FM) signals, was realized in optoelectronic modules. Firstly, FM monitoring receiver DB4004 was used to collect FM signals; Secondly, FM signals were preprocessed and analyzed to build a FM dataset. Finally, weighted centroid k-nearest neighbors (WC-KNN) precise positioning algorithm was proposed to obtain the position information of the photoelectric module. Experimental results showed that the median location error of the WC-KNN algorithm can reach 0.8 meters and additional hardware equipment was not required. The research results provided the feasibility for the practical application of equipment based on optoelectronic devices in various fields.